Sporadic Parkinson’s Disease Potential Risk Loci Identified in Han Ancestry of Chinese Mainland - Wang, Bo; Liu, Xin; Xu, Shengyuan; Liu, Zheng; Zhu, Yu; Zhang, Xiong; Xu, Renshi (Frontiers in Aging Neuroscience, 2021)
Recent investigations demonstrated that genetic factors might play an important role in sporadic Parkinson’s disease (sPD). To clarify the specific loci susceptibility to sPD, we analyze relationship between 30 candidate single nucleotide polymorphisms (SNPs) and sPD in the population of Han ancestry from Chinese mainland (HACM) by using genome-wide association study, sequenom massARRAY, DNA sequence and biological information analysis. Results showed that the subjects carrying the T allele of rs863108 and rs28499371 exhibited a decreased risk for sPD. The subjects carrying the T allele of rs80315856 exhibited an increased risk for sPD. The A/T genotype of rs863108 and the C/T genotype of rs28499371 were a potential increased risk for sPD, and the G/T genotype of rs80315856 and T/T genotype of rs2270568 were a potential decreased risk for sPD. The minor allele frequency (MAF) of rs80315856 and rs2270568 was higher in sPD. The T allele of rs80315856 and rs2270568 might be a risk locus for sPD. Our data suggested that the alteration of these SNPs might play some roles through changing/affecting LINC01524/LOC105372666, DMRT2/SMARCA2, PLEKHN1 and FLJ23172/ FNDC3B genes in the pathogenesis of sPD.